Automatic Deployment of Network Security in AWS Cloud Infrastructure - Hartikainen, Albert (My University, 2025)
Large scale changes to network infrastructure sometimes need to be implemented within a short period of time. This means that it is crucial to have the processes necessary to create the needed security architecture with it, making it practically required that they are defined and automated beforehand. This thesis aims to create said automation, based on relevant research and industry standards. There are many frameworks which can be used as a basis for concrete security configurations. As the cloud providers have a vested interest in having the services running on their services be secure, using their frameworks as a base works as a starting point. Any configuration will need to be customized for each individual system to achieve optimal security. This thesis shows a way to automate the deployment of AWS security features in a manner agnostic to both application and scale. The solution provides a baseline level of security and can be modified and configured to fit many different types of networks.
Keywords: network security, cloud infrastructure, automation, AWS